Manufacturing strategies for wafer-scale two-dimensional transition metal dichalcogenide heterolayers. Issue 11 (15th June 2020) - Wang, Mengjing; Li, Hao; Ko, Tae-Jun; Sumaiya Shawkat, Mashiyat; Okogbue, Emmanuel; Yoo, Changhyeon; Han, Sang Sub; Islam, Md Ashraful; Oh, Kyu Hwan; Jung, Yeonwoong
Abstract: Abstract : Modern electronics have been geared toward exploring novel electronic materials that can encompass a broad set of unusual functionalities absent in conventional platforms. In this regard, two-dimensional (2D) transition metal dichalcogenide (TMD) semiconductors are highly promising, owing to their large mechanical resilience coupled with superior transport properties and van der Waals (vdW) attraction-enabled relaxed assembly. Moreover, 2D TMD heterolayers based on chemically distinct constituent layers exhibit even more intriguing properties beyond their mono-component counterparts, which can materialize only when they are manufactured on a technologically practical wafer-scale. This mini-review provides a comprehensive overview of recent progress in exploring wafer-scale 2D TMD heterolayers of various kinds. It extensively surveys a variety of manufacturing strategies and discusses their scientific working principles, resulting 2D TMD heterolayers, their material properties, and device applications. Moreover, it offers extended discussion on remaining challenges and future outlooks toward further improving the material quality of 2D TMD heterolayers in both material and manufacturing aspects.